2020
DOI: 10.1038/s41420-020-0237-8
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical studies reveal MLN4924 is a promising new retinoblastoma therapy

Abstract: RB1 loss (RB1 null ) or MYCN amplification (MYCN amp ) in fetal human retina causes retinoblastoma. SKP2 loss kills RB1 null cells, but small molecule SKP2 inhibitors remain unexplored therapeutically. Whether SKP2 is synthetic lethal in MYCN amp retinoblastoma is unclear. SKP2 is the substrate recognition component of two Cullin-RING Ligase complexes (CRL1 SKP2 /SCF SKP2 , and CRL4 SKP2 ), a family of multiprotein E3 ubiquitin ligases. NEDD8 activating enzyme (NAE) is required for Cullin neddylation and thus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…Functional loss of SKP2 has a synthetic lethal effect in RB1 -deficient tumors including retinoblastoma [ 71 , 76 , 77 , 156 ]. SKP2 inhibitors that prevent SKP2 binding to the SCF (Skp1-Cullin1-F-box) core subunit inhibit proliferation of retinoblastoma cells, but the potency of currently synthesized inhibitors is poor [ 157 ]. Pevonedistat (MLN4924) suppresses NEDD8-activating enzyme E1 activity in neddylation of Cullin1, thereby dampening SCF activity [ 158 ].…”
Section: Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional loss of SKP2 has a synthetic lethal effect in RB1 -deficient tumors including retinoblastoma [ 71 , 76 , 77 , 156 ]. SKP2 inhibitors that prevent SKP2 binding to the SCF (Skp1-Cullin1-F-box) core subunit inhibit proliferation of retinoblastoma cells, but the potency of currently synthesized inhibitors is poor [ 157 ]. Pevonedistat (MLN4924) suppresses NEDD8-activating enzyme E1 activity in neddylation of Cullin1, thereby dampening SCF activity [ 158 ].…”
Section: Treatmentsmentioning
confidence: 99%
“…Pevonedistat (MLN4924) suppresses NEDD8-activating enzyme E1 activity in neddylation of Cullin1, thereby dampening SCF activity [ 158 ]. Pevonedistat tested in clinical trials for treatment of many cancers potently suppresses the growth of retinoblastoma with minimal off-target effects via intravitreal delivery in orthotopic xenograft models [ 157 , 158 ]. The drug exerts a broad range of activities from cytostatic to lethal in multiple retinoblastoma cell lines, regardless of the RB1 or MYCN status [ 157 ].…”
Section: Treatmentsmentioning
confidence: 99%
“…SKP2, a component of the SCF SKP2 ubiquitylating complex, is another promising hub as its loss is synthetic lethal in many RB1 null contexts, including RB [ 16 ]. Indeed, blocking activation of the SCF SKP2 complex with the neddylation inhibitor MLN4924 (Pevonedistat) shows promise as a new RB therapy [ 17 ]. Such studies illustrate the value in dissecting networks that drive RB cell growth and survival to identify novel therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…This small molecule is an adenosine sulfamate analog that covalently binds to NAE to create a NEDD8-MLN4924 adduct, consequently blocking neddylation of all cullin-RING ligases (CRLs), which regulate the destruction of many intracellular proteins. Inhibition of CRL neddylation suppresses cancer cell growth by increasing the levels of their substrates, which in turn triggers the DNA damage response, cell-cycle arrest, apoptosis and autophagy (Aubry et al 2020 ). MLN4924 has been applied in several phase I clinical trials for certain solid tumors and hematologic malignancies and showed clinical activity in a phase I clinical trial of acute myelogenous leukemia (AML) (Swords et al 2010 ).…”
Section: Inhibitors Of Ubiquitinating Enzymes-clinical Trialsmentioning
confidence: 99%